The Integration of Cloud-Based Portfolios and Project-Based Learning to Foster Speaking Performance and 4C Skills in EFL Classroom - Ela Kristi Permatasari; Zaky Dzulhiza Hawin Amalia; Lutfiana; Alfia Desti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The impact of incorporating cloud-based portfolios into Project-Based Learning (PBL) to enhance senior high school students’ English-speaking proficiency and 4C skills-critical thinking, creativity, communication, and collaboration is examined in this study. The study, which employed an explanatory sequential mixed-methods design, involved 72 students from two public senior high schools in Central Java, Indonesia. Participants were assigned to the experimental and control groups using purposive sampling. Speaking performance tests were used to get quantitative data during pre-test, Project 1, Project 2, and post-test activities. Questionnaires and semi-structured interviews with English teachers were used to gather qualitative data. According to the results, students in the experimental groups showed progressive improvement in speaking performance across Project 1, Project 2 and Post-test activities. Through group projects, reflective learning, feedback cycles, and genuine speaking exercises, the incorporation of cloud-based portfolios promoted the development of 4C abilities. Students expressed positive attitudes about adopting cloud-based portfolios, particularly when it came to enhancing learner autonomy, motivation, creativity, and communication, according to the questionnaire answers. Additionally, the results of the interviews demonstrated that the integrated instructional model transformed teachers’ responsibilities into learning facilitators while boosting students’ confidence, engagement, and active participation in speaking activities. A cloud-based e-portfolio template, an analytical rubric for speaking and 4C assessment, and an instructional framework combining PBL with cloud-based portfolios are just a few of the educational outputs that this study created in addition to its empirical findings. The study comes to the conclusion that incorporating cloud-based portfolios into PBL improves speaking development and 21st-century skills in EFL courses.